Gambaran Praktik Five Moment Cuci Tangan Pada Perawat Di Puskesmas - Hilmawaty Susanthy Kue Paudi (State University of Gorontalo, 2022)
The prevalence of nosocomial infections around the world is a serious concern for all health services, especially in hospitals. One of the contributing factors is non-compliance in the implementation of handwashing procedures in accordance with standard operating procedures. The study aims to determine the level of compliance of nurses in the implementation of the five-moment Handwashing at the Dungingi Health Center in 2020. The design used is obsevasional descriptive with a cross sectional approach. The total sample was 97 people taken by purposive sampling . The data analysis carried out in this study is univariate data analysts. The results of the study found that most respondents had a compliance rate of less than 69.1%, moderate compliance as much as 18.6% and good compliance as much as 12.4%. It is recommended that all nurses be more concerned about the importance of implementing the five-moment hand hygiene standard procedure, and the Puskesmas provides rewards to nurses who are obedient in implementing these standards.